Diagnostic and therapeutic challenge of unclassifiable enteropathies with increased intraepithelial CD103+ CD8+ T lymphocytes: a single center case series. (3rd August 2021) - Hartl, Christina; Finke, Jürgen; Hasselblatt, Peter; Kreisel, Wolfgang; Schmitt-Graeff, Annette
Abstract: Objectives: Chronic diarrhea, villous atrophy and/or increased intraepithelial T-lymphocytes (IEL) occur in many inflammatory disorders including celiac disease (CD). However, a definite diagnosis is difficult to make in some patients despite an extensive diagnostic work-up. Clinical outcomes and histological phenotypes of such patients we refer to as unclassifiable enteropathy (UEP) remain unclear. Material and methods: We performed a retrospective single-center analysis of patients with chronic diarrhea, weight loss and increased IEL. Patients with defined etiologies including infections, CD, drugs, immunodeficiencies or neoplasms were excluded. Clinical and histologic/immunophenotypic parameters were analyzed. Results: Nine patients with UEP were identified. Small intestinal damage ranged from minor villous abnormalities to complete atrophy while all patients displayed high numbers of CD103 + CD8 + IELs. In contrast to CD, these CD8 + T cells were not confined to the surface epithelium, but also infiltrated the crypts. Additional histological features included apoptotic crypt epithelial cells and mixed inflammatory infiltrates in the tunica propria. Involvement of other segments of the gastrointestinal tract was observed in 7/9 patients. A clonal intestinal T-cell lymphoproliferative disorder developed in 2 patients, one of which had a fatal disease course. The majority of patients responded to corticosteroids, while response to immunosuppressive medications yielded heterogeneous results. Conclusions: We report a patient population with 'difficult-to-classify' enteropathies characterized by various degrees of villous atrophy and strongly increased intraepithelial CD103 + CD8 + T cells in the small intestine which harbor an increased risk for T-cell lymphoproliferative disorders. Clinical course, histology, and response to immunosuppressive therapy all suggest an autoimmune pathogenesis.